2021
DOI: 10.1002/pssa.202000804
|View full text |Cite
|
Sign up to set email alerts
|

Indium Tin Oxide with High Carrier‐Collection Capacity and Radiation Resistance for GaInP Solar Cell

Abstract: The crystal structure, light transmittance, and contact resistivity of transparent conducting indium-tin-oxide (ITO) films for a III-V solar cell are studied. The optical transparency of ITO can reach 96% under appropriate annealing conditions. ITO and n þ -GaAs can form Ohmic contacts having a lower contact resistance than those formed with ITO and n þ -GaInP. A specially designed solar cell structure is fabricated to grow the ITO film as the front electrode and thus prevent oxidation of the AlInP window laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In the literature, several articles were reported based on the study of the shielding properties of indiumcontaining oxide and non-oxide glasses [14][15][16][17][18][19][20][21][22][23][24] but no report of indium-containing non-oxide chalcogenide glasses was found. Dai et al observed the high collection carrier capacity of indium tin oxide (ITO) film by irradiating it with 1 MeV energy and suggested that ITO film can be applied in the manufacturing of space solar cells [14]. The shielding properties of indium oxide glass for electromagnetic interference (EMI) applications were studied by Asbalter et al [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, several articles were reported based on the study of the shielding properties of indiumcontaining oxide and non-oxide glasses [14][15][16][17][18][19][20][21][22][23][24] but no report of indium-containing non-oxide chalcogenide glasses was found. Dai et al observed the high collection carrier capacity of indium tin oxide (ITO) film by irradiating it with 1 MeV energy and suggested that ITO film can be applied in the manufacturing of space solar cells [14]. The shielding properties of indium oxide glass for electromagnetic interference (EMI) applications were studied by Asbalter et al [15].…”
Section: Introductionmentioning
confidence: 99%
“…ITO film also has good electrical conductivity and can be used as an ohmic contact [5]. Beside, ITO electrode has a strong capacity for carrier collection [6]. The dielectric chosen is Al2O3 has outstanding stability, high dielectric strength, resilience under harsh conditions and high transparency [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies that explain the synthesis and characterization of various materials are very interesting for researchers to study, especially those using the basic precursor material, namely SnO2, where these materials are closely related to various technologies that support community needs, which of course will increase and develop every year . SnO2 is widely applied to electronic devices such as diodes (Lee et al, 2019), transistors (Dou et al, 2019), capacitors (Dai et al, 2021), solar cells (Mikolášek, 2017;Altinkaya et al, 2021;Luo et al, 2022), liquid crystal displays (Zhang et al, 2021;Chu et al, 2021;, gas sensors (Zhou et al, 2018;Karabulut et al, 2018), and other optoelectronic equipment (Rana et al, 2019).…”
Section: Introductionmentioning
confidence: 99%